INFLUENCE MIX MARKETING 4P (PRODUCT, PRICE, PLACE, PROMOTION) ON CONSUMER DECISIONS TO CHOOSE COFFEE MEMORY - Wilbert Alexander; Chinxie Giovanni Cadet; Rosinta Romauli Situmeang; Firmansyah (Mount Hope Economic Global Journal, 2025)
Kopi Kenangan, although known for its contemporary milk coffee menu and more affordable prices compared to international outlets, faces several challenges in Medan. Local consumer preferences that tend to prefer classic coffee flavors such as tubruk coffee or espresso have not been fully accommodated. In addition, the price of the product is still considered relatively expensive by the middle segment when compared to traditional coffee shops. The location of the outlet is less strategic and the promotion is less effective also become obstacles in attracting consumer interest and loyalty in this competitive market. The population used in this study were all consumers who made purchases at the company where the number is not known for sure. Due to the unknown population, the sampling technique used was the Lemeshow formula with an error rate of 10% where 96 research samples were obtained. The results of the study showed that the Product influences Consumer Decisions to Choose Kopi Kenangan. Price influences Consumer Decisions to Choose Kopi Kenangan. Location influences Consumer Decisions to Choose Kopi Kenangan. Promotion influences Consumer Decisions to Choose Kopi Kenangan. Product, Price, Location and Promotion influence Consumer Decisions to Choose Kopi Kenangan